2014
DOI: 10.3389/fmars.2014.00079
|View full text |Cite
|
Sign up to set email alerts
|

Spatial gradients in trace metal concentrations in the surface microlayer of the Mediterranean Sea

Abstract: The relationship between dust deposition and surface water metal concentrations is poorly understood. Dissolution, solubility, and partitioning reactions of trace metals from dust particles are governed by complex chemical, biological, and physical processes occurring in the surface ocean. Despite that, the role of the sea surface microlayer (SML), a thin, but fundamental component modulating the air-sea exchange of materials has not been properly evaluated. Our study revealed that the SML of the Mediterranean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Metal aerosol compositions are shown in Table 1. The range (ng/m 3 ) of concentrations in our study (Cd: 0 -0.2 , Co: 0.05 -0.3 , Cu: 0.4 -4.8, Fe: 23 -266, Ni: 1.6 -7.1, Mo: 0.0 -2.1, V: 3 -18, Zn: 2.0 -14.6 and Pb: 0.2 -7.0) was of the same order of magnitude of previous measurements collected in the same region and season (Becagli et al, 2012;Calzolai et al, 2015, p.10;Guerzoni et al, 1997;Tovar-Sánchez et al, 2014;Heimbürger et al, 2010), and were therefore consistent with Western Mediterranean background concentrations. However, it has been shown that aerosol concentrations of anthropogenic trace metals (i.e.…”
Section: Aerosols Depositionssupporting
confidence: 83%
See 2 more Smart Citations
“…Metal aerosol compositions are shown in Table 1. The range (ng/m 3 ) of concentrations in our study (Cd: 0 -0.2 , Co: 0.05 -0.3 , Cu: 0.4 -4.8, Fe: 23 -266, Ni: 1.6 -7.1, Mo: 0.0 -2.1, V: 3 -18, Zn: 2.0 -14.6 and Pb: 0.2 -7.0) was of the same order of magnitude of previous measurements collected in the same region and season (Becagli et al, 2012;Calzolai et al, 2015, p.10;Guerzoni et al, 1997;Tovar-Sánchez et al, 2014;Heimbürger et al, 2010), and were therefore consistent with Western Mediterranean background concentrations. However, it has been shown that aerosol concentrations of anthropogenic trace metals (i.e.…”
Section: Aerosols Depositionssupporting
confidence: 83%
“…Trace metal concentrations of T-SML (Table 1), with the exception of Pb, were lower, although, of the same order of magnitude, than those measured in a previous study carried out in the MS (Tovar-Sánchez et al, 2014). This lower content of metals in the SML is probably related to the lower dust aerosol deposition during our sampling period and to the lack of influence of desert dust aerosols except for the Fast station.…”
Section: Trace Metals In the Smlsupporting
confidence: 37%
See 1 more Smart Citation
“…Despite these indirect evidences on the biological importance of Co, its biogeochemistry is poorly documented in the MS. Previously reported DCo surface concentrations are elevated compared to other oligotrophic domains and increase eastward from the Western Basin to the Aegean Sea [ Tovar‐Sánchez et al , ]. Atmospheric inputs and Gibraltar Strait surface fluxes are thought to be the main sources and scavenging to be the main sink of DCo [ Zhang et al , ; Guieu et al , ; Elbaz‐Poulichet et al , , ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aerosol derived N and P input, other micronutrients from the aerosols may also be limiting factors for microbial activity (e.g., Paytan et al, 2009). Tovar-sánchez et al (2014) showed that Fe originating from aerosol particles was found to be unevenly distributed between the SML and SSL following a dust storm event. Thus, when considering the results described here and the work presented by Tovar-sánchez and collegues, we assume that aerosol depositions may trigger different impacts in these distinct layers.…”
Section: Sml Bacterioplankton Enrichmentmentioning
confidence: 99%